Enforcement of Norms of Women's Representation in The Regional House of Representatives of Pekalongan Regency, Period 2019-2024 - Teti Hadiati; Eni Purwanti (Asian Journal of Law and Humanity, 2022)
This Paper analyzes about enforcement the norm of women's representation in the Regional House of Representatives of Pekalongan Regency for the period 2019-2024 and its implications for regional policies related to women's issues. Empirical juridical research uses a qualitative approach. Data collection techniques using interviews, questionnaire and the documents studies. Technical analysis using interactive models. The results showed that, enforcement norms of woman’s representation in the Regional House of Representatives of Pekalongan Regency for the period 2019-2024 not effective because there are several factors that influence it, among others: 1) the substance of the norms of representation of 30% women in the legislative institutions contained in the electoral law is inconsistent because if the registration of political parties participants does not the requirements of 30% of Women's representation, political parties are allowed to improve the proposed candidates. The norm will make political parties election participants in recruiting Women as an only formality with jargon " the important thing is fulfilled” without regard to the quality of Women's participants; 2) Knowledge and understanding of Pekalongan District community about women's politics are still low, so that if women run for election participants then very small supporters; 3) patriarchal legal culture build a mindset that the political world is identical with a man. The implications of enforcing the norm of 30% of women's representation in the Regional House of Representatives of Pekalongan Regency , namely being able to represent women's voices and fight for women's rights through policies and programs produced. That is, with the representation of women in regional House of Representatives, the needs of women will be met because those who know and understand the needs and problems of women are women themselves.